Gas demand in times of crisis. The response of German households and industry to the 2021/22 energy crisis - Oliver Ruhnau; Clemens Stiewe; Jarusch Muessel; Lion Hirth (ZBW – Leibniz Information Centre for Economics, 2022)
Europe is in the midst of the most severe energy crisis in a generation, at the core of which is the continuously plummeting supply of Russian natural gas. With alternative supply options being limited, natural gas prices have surged. This paper empirically estimates the response of natural gas demand to the price increase, using data from Germany—the so far largest consumer of Russian natural gas. We identify the crisis response of small and large consumers separately, controlling for temperature, gas-fired power generation, and economic activity. For small consumers, including mostly households, we find a substantial demand reduction of 6% from March onwards—most likely due to political and ethical considerations after the start of Russia's invasion of Ukraine. For industrial consumers, demand reductions started much earlier in August 2021, when wholesale prices for natural gas started to surge, with an average reduction of 11%. We conclude that voluntary industrial demand response has played a significant role in coping with the energy crisis so far.
More recent version: http://hdl.handle.net/10419/265522
Keywords: Q41; 330; Energy demand; Demand response; European energy crisis; Natural gas